Apache Jakarta Commons: Reusable Java™ Components - Iverson, Will (Bruce Perens' Open Source series., 2005)
Easy-to-follow coverage of twelve indispensable Jakarta Commons packages Code examples that show innovative uses of Commons components, including using HttpClient to access Web resources, FileUpload for handling HTTP file uploads, and BeanUtils for easy form generation Detailed instructions for combining the Commons project libraries with the popular Eclipse IDE Save time and money with reusable open source Java™ components Master the Jakarta Commons Library of Open Source JavaTM Components Using the Apache Jakarta Commons reusable Java™ components, you can leverage the work of the global open-source community to solve common programming problems reliably, quickly, and inexpensively. But, to use the Commons libraries effectively, you need far more guidance than the official documentation offers. In Apache Jakarta Commons: Reusable Java™ Components, Will Iverson covers what Java developers need to know to take full advantage of Jakarta Commons-starting right now. Iverson begins with a definitive overview of the Commons project: goals, installation, and getting started with Commons components. Next, he presents example-rich chapters on the twelve most useful Commons packages, covering topics ranging from HTTP FileUpload to database connectivity. Iverson provides detailed code samples for every component he describes. After you've mastered the core Jakarta Commons packages, you'll constantly rely on this book's handy seventy-five page quick-reference. Iverson's coverage includes Downloading Commons project libraries and installing them into Eclipse Programmatically accessing resources via HTTP, FTP, NNTP, and other Internet protocols Using the Jakarta Commons suite of configurable object pools Managing database connectivity in Swing applications-and anywhere containers aren't doing it for you Using BeanUtils to generate forms and gain runtime access to information provided by JavaBeans-style objects Traversing complex object graphs with JXPath Using Jakarta Commons' advanced collections tools to establish richer object relationships Extending java.lang with better methods for manipulating core classes Implementing conversion routines, configurable logging, command-line help, and more Exploring the newest packages, including emerging "sandbox" packages Whether you're building code for front-end Web applications, client-side software, or back-end servers, learning Jakarta Commons will make you far more efficient. Apache Jakarta Commons is the faste...